A mmWave JCAS System for Real-Time High-Data Rate Communication and RADAR Sensing - Markus Petri; Nebojsa Maletic (IEEE Access, 2025)
This paper presents a real-time millimeter-wave (mmWave) joint communication and sensing (JCAS) system, supporting bi-directional data communication with up to 5.8 Gbit/s coded data rate as well as mono-static radio detection and ranging (RADAR) with a range resolution of 6.7 cm and up to 2.1 kHz sensing rate. The same hardware resources, i.e., an orthogonal frequency-division multiplexing (OFDM) baseband processor and a beam-steering phased array antenna frontend, the same signal waveform and the same frequency channel are used for both sensing and communication. After a description of one intended use case and the design constraints, the system architecture is described in detail. The focus is on two main modules, i.e. the advanced extensible interface 4 (AXI4) stream crossbar switch and the sensing controller, while changes of the basic OFDM baseband processor design are also explained. For the sensing function, the used hardware-based OFDM baseband processor does not provide a sufficiently precise synchronization of received frames, so a method for the temporal alignment of the received channel impulse responses (CIRs) for different beams is developed and assessed. The evaluation of the system performance and the measurement results highlight that it is possible to perform very precise sensing with an OFDM baseband processor purely developed for data communication. The presented method for the CIR alignment does not depend on the baseband signal processing and can be used in any JCAS system with full duplex sensing.